2017
DOI: 10.1021/acs.jpcb.7b08233
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Permeability of Fatty Acyl Compounds Studied via Molecular Simulation

Abstract: Interest in fatty acid-derived products as fuel and chemical precursors has grown substantially. Microbes can be genetically engineered to produce fatty acid-derived products that are able to cross host membranes and can be extracted into an applied organic overlay. This process is thought to be passive, with a rate dependent on the chemistry of the crossing compound. The relationship between the chemical composition and the energetics and kinetics of product accumulation within the overlay is not well underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(52 citation statements)
references
References 97 publications
4
45
3
Order By: Relevance
“…Most compounds tested were on the higher end of this permeability spectrum, with carboxylates and glycosylated LRCs being among the least permeable compounds. Breaking down the permeabilities into a interleaflet transition/membrane crossing step (Pmc) and an extraction step (Pme ) reveals that crossing rather than extraction is typically the rate-limiting step to membrane permeation (SI Appendix, Tables S1-S3), in contrast to earlier findings for fatty acyl products or terpenoids (33,34). Only for highly processed aromatic compounds, such as benzenes or cresols, or specific LRC dimers with few hydroxy groups to retard membrane crossing (5-5 and 4-O-5 linkages), is Pmc > Pme .…”
Section: Resultscontrasting
confidence: 63%
“…Most compounds tested were on the higher end of this permeability spectrum, with carboxylates and glycosylated LRCs being among the least permeable compounds. Breaking down the permeabilities into a interleaflet transition/membrane crossing step (Pmc) and an extraction step (Pme ) reveals that crossing rather than extraction is typically the rate-limiting step to membrane permeation (SI Appendix, Tables S1-S3), in contrast to earlier findings for fatty acyl products or terpenoids (33,34). Only for highly processed aromatic compounds, such as benzenes or cresols, or specific LRC dimers with few hydroxy groups to retard membrane crossing (5-5 and 4-O-5 linkages), is Pmc > Pme .…”
Section: Resultscontrasting
confidence: 63%
“…Interactions of surfactants with lipid membranes have been investigated in the past. Vermaas et al (2017) studied membrane permeation by alkyl fatty acids compared to alcohols, aldehydes, and alkyl chains, and their extraction into a dodecane layer using atomistic MD simulations. They observed that transfer of fatty acid and alcohol between the membrane leaflet is slower compared to the other compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Two factors affecting gas adsorption, free volume and intermolecular attractive energy were found; Josh et al. computed the membrane permeability coefficients of different fatty acyl products through molecular dynamics (MD). And they identified specific interactions that accelerate aldehydes transit across the membrane bilayer; Sadiye et al.…”
Section: Introductionmentioning
confidence: 99%
“…Chang et al [27] analyzed gas sorption behavior in the polyimide membrane via Monte Carlo (MC) technique. Two factors affecting gas adsorption, free volume and intermolecular attractive energy were found; Josh et al computed the membrane permeability coefficients of different fatty acyl products through molecular dynamics (MD) [28] . And they identified specific interactions that accelerate aldehydes transit across the membrane bilayer; Sadiye et al used molecular simulation techniques to gain insight on sorption induced changes in the polymer matrices [29] .…”
Section: Introductionmentioning
confidence: 99%